The Intimate Link between Income Levels and Life Expectancy: Global Evidence from 213 Years - Michael Jetter; Sabine Laudage; David Stadelmann (Institute for the Study of Labor (IZA), 2016)
Contrary to previous findings, we find a systematic and economically sizeable relationship between income levels and life expectancy in a panel dataset of 197 countries over 213 years. By itself, GDP/capita explains more than 64 percent of the variation in life expectancy. The Preston curve prevails, even when accounting for country- and time-fixed effects, country-specific time trends, and alternative control variables. Quantile regressions and instrumental variable estimations suggest this link to be persistent across different levels of life expectancy and unaffected by reverse causality. If policymakers want to prolong people's lives, economic growth appears to be the predominant medicine.
Keywords: I15; I31; J11; H51; 330; historical panel data; income levels; life expectancy; quantile regression analysis